Adenine-based bio-MOFs with high water and acid–base stability for ammonia capture. Issue 42 (12th October 2022) - Ruan, Mingming; Li, Anqi; Wen, Yaping; Zhou, Lian; Zhang, Jun; Xuan, Xiaopeng
Abstract : Two isoreticular bio-MOFs with high thermal and chemical stabilities were constructed. They exhibit a large uptake of about 7–10 mmol g −1 at 1 bar and can serve as promising sorbents for NH3 . Abstract : Ammonia capture is of great importance to environmental protection and resource conservation. In this work, two isoreticular bio-MOFs, namely, Zn(3-AIN)(AD)·DMF and Zn(3-AIN)(AD)·DMA, were constructed with inexpensive, easily available and low-toxicity/non-toxic ligands and Zn 2+ in different solvents, respectively. They possess 1D channels decorated by four free amine groups and N atoms from pyrimidine rings and can retain their crystallinity and porosity even after soaking in boiling water for 4 hours and in aqueous solution with various pH values ranging from 1 to 14. These two bio-MOFs can serve as promising sorbents for NH3, exhibiting a large uptake of about 7–10 mmol g −1 at 1 bar.